Network device ad-blocker - Mohamad, Juhaina; Abdullah, Zeyana; Mohd Nasir, Fawwaz (Penerbit UTHM, 2020)
While surfing the web, users are frequently bombarded with the abundance of digital advertisements, or simply called ads, in the form of images and videos. These often unwanted and sometimes obnoxious ads can be blocked by installing an often lagging ad-blocker in the web browser on your computer. This becomes even complicated in smartphones and tablets, as ads can also appear in other apps. Therefore, this project introduces the Network Device Ad-Blocker hardware to overcome the mentioned problems. The Rapid Application Development (RAD) methodology is used to realize this project. Subsequent testing shows that no ads appear after the deployment this hardware with significant improvements in the download speed.